Essentials of Chinese Literature and Art Criticism Volume I
XXI, 378 p. 13 illus., 5 illus. in color.
Keywords: This book offers a detailed analysis of China’s original view of literature and art theory and critical practice from the ancient to the modern period, providing views on dancing, image making, the circulation of artifacts, critical theory, creative writing, art design, aesthetic, cyber arts, photography, etc. This book makes visible the traditional Chinese ideas, philosophy and practices on literature and art in the world and contributes to the diversity of current international literary and art studies. All 15 chapters are translations of selected high-quality original theoretical contributions on Chinese literary and art theory published in prestigious peer-reviewed Chinese journals, whose authors are established scholars in Chinese academia. Xu Yuechun is at China Federation of Literary and Art Circles, Center for Literature and Art Criticism, Beijing, China. Wang Ning is at Shanghai Jiao Tong University, School of Humanities, Shanghai, China.